Respuestas

2012-11-21T03:26:37+01:00

tendrias q despejar tanto x como z de la ecuacion 1 y 2 y luego reemplazarlas en la ecuacion 3 .. 

 

1) ctg x=3/4 ==>   x = arcCtg 3/4   


2) tg z= 8/15 ==>  z = arcTg 8/15


3) sen(x+z) /sen x . cos z   ==> [sen (arcCtg 3/4 + arcTg 8/15)] / sen (arcCtg 3/4) . cos(arcTg 8/15)

 

solo remplaza x=arcCtg 3/4  y  z=arcTg 8/15 en la ecuacion 3 .saludos

2012-11-21T03:31:25+01:00

cosx/senx= 3k/4k

senz/cosz= 8k/15k

- sen(x+z)=senx.cosz+senz.cosx

reemplazando:

senx.cosz+senz.cosx/senx.cosz   +  3/5

4k*15k+8k*3k/4k*15k  + 3/5

simplificando, sale:

84/60 + 3/5 = 7/5 + 3/5 = 2...Rpta.2